1999
DOI: 10.1152/jappl.1999.87.1.36
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of inspiratory pressure drop in neonatal and pediatric endotracheal tubes

Abstract: Endotracheal tubes (ETTs) constitute a resistive extra load for intubated patients. The ETT pressure drop (DeltaP(ETT)) is usually described by empirical equations that are specific to one ETT only. Our laboratory previously showed that, in adult ETTs, DeltaP(ETT) is given by the Blasius formula (F. Lofaso, B. Louis, L. Brochard, A. Harf, and D. Isabey. Am. Rev. Respir. Dis. 146: 974-979, 1992). Here, we also propose a general formulation for neonatal and pediatric ETTs on the basis of adimensional analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 23 publications
(42 reference statements)
1
41
0
1
Order By: Relevance
“…Apart from the inertance component, it thus is similar to their method of calculating the pressure fall in the adult setting (3). Jarreau et al (4) presented another approach to indirect measurement by dividing the total pressure drop into a fraction owing to loss of kinetic energy at entry and exit of tube, and a fraction owing to viscous pressure drop. The kinetic energy loss may be approximated by various equations (5), but its actual value is best estimated in the actual setting by subtracting the viscous pressure from the total pressure drop.…”
mentioning
confidence: 99%
“…Apart from the inertance component, it thus is similar to their method of calculating the pressure fall in the adult setting (3). Jarreau et al (4) presented another approach to indirect measurement by dividing the total pressure drop into a fraction owing to loss of kinetic energy at entry and exit of tube, and a fraction owing to viscous pressure drop. The kinetic energy loss may be approximated by various equations (5), but its actual value is best estimated in the actual setting by subtracting the viscous pressure from the total pressure drop.…”
mentioning
confidence: 99%
“…Jarreau et al 30 reported that the mean range of ETT curvature diameters from magnetic resonance imaging scans were 8-18 cm with a ,16% variation in pressure between these extremes. Both of the studied curves present in the ETT, which can be seen in Figure 2, 31 were within these parameters.…”
Section: Airflow Analysismentioning
confidence: 99%
“…32 To better evaluate the computational model, the critical Reynold's number was calculated according to the following formula proposed in Jarreau et al, where D is the diameter of the tube and R c is the radius of curvature. 30 The critical Reynolds number is 5668. The approximations for the fluid model also assumed quasistatic flow in the ETT.…”
Section: Airflow Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Critical Reynolds numbers (i.e. Reynolds numbers for which flow pattern change) are known for small ETT in natural curvature and without entry flow (Jarreau et al, 1999). These critical Reynolds numbers are unknown for adult ETT, under both laboratory and clinical conditions.…”
Section: Introductionmentioning
confidence: 99%